Research on Functional Mathematical Literacy of Pupils with Moderate Special Educational Needs Learning in Mainstream Schools - Tomėnienė, Laima (Social Welfare: Interdisciplinary Approach, 2013)
The article deals with the research on functional mathematical literacy of pupils with moderate special educational needs (SEN) learning in eighth forms of mainstream schools. Research data were collected applying quantitative approach. The article describes aspects of research structure, material selection and received research results. The questionnaire survey was employed to fnd out how pupils with moderate SEN learning in eighth forms of mainstream schools are able to apply existing mathematical knowledge in real-life situations and solving practical type problems, their functional mathematical literacy abilities are assessed.
Keywords: functional abilities; mathematical achievements; mathematical literacy; pupils with moderate special educational needs